A educação popular para o cuidado em saúde ante a morte e o morrer a partir de experiências, reflexões e aprendizados de profissionais de saúde - Vasconcelos, Marcos Oliveira Dias (2021)
In the last decades, the subject of care in the face of death and dying has deserved many scientific studies and publications. However, health practices and services are still far from the shared construction of integral care for people with life-threatening illnesses and their families. This qualitative approach research aims at investigating contributions from Popular Education to health care in the face of death and dying, from experiences, learning and reflections of health professionals, who work in the city of João Pessoa - PB, Brazil, who had a previous training marked by Popular Education. Popular Education was the theoretical and methodological framework used in this research. Hermeneutic was the basis for the analysis and interpretation of the narratives. The in-depth interview with a previous script was used as a methodological strategy. It was found that the participation in experiences guided by Popular Education had an impact on the training of health professionals through the creation of a strong affective and political bond with people, groups and popular communities, which did their best in the search and creation of health practices more integrated to interests, worldviews and living conditions of the population. Various contributions from Popular Education to improve care in the face of death and dying have been systematized based on health professionals’ practical experiences, reflections and learning, bringing innovations in relation to the reflections and recent advances in thanatology and palliative medicine. Popular Education broadens the view and understanding of dealing with death and dying, not only because it seeks to integrate knowledge from the human and social sciences with those accumulated by different health professions, but, mainly, due to its investment in listening and dialogue with the people under care. This enriches health practices with very peculiar values, knowledge, interests and initiatives from the different people and social groups involved in each concrete situation. Thus, there is a reading of the reality and construction of care practices that go far beyond interdisciplinarity and interprofessionality. Popular Education integrates conscious and logically structured knowledge with knowledge from emotion, intuition, spirituality and love. It integrates academically systematized knowledge derived from the experience lived and reflected locally. Thus, it constitutes a true epistemological conversion in the production of health knowledge. By investing in sensitive and committed listening to people's life stories and contexts, Popular Education also becomes a different way of thinking and being in the lives of different health professionals. The power of what is learned and what is built and shared with the people and families that are cared for, provides a radical change in the care model. By emphasizing the legitimacy and investing in the role of the people and groups under care, especially those silenced and marginalized, it contributes to a more just, solidary and democratic society. Health care in the face of death and dying, as it is a time of intense mobilization, has great educational potential and to change the previous ways of living and traditions of care.